THE PROGNOSIS IN TRANSCATHETER AORTIC VALVE IMPLANTATION - T. E. Imaev; A. E. Komlev; R. S. Akchurin (Рациональная фармакотерапия в кардиологии)
Aim. To study the effect of transcatheter aortic valve implantation (TAVI), performed by different types of prostheses and various surgical access, on the prognosis of patients with critical aortic stenosis and comorbidities.Material and methods. Patients (n=130) that had consistently performed 80 TAVI by Edwards valve transfemoral (n=50) and transapical (n=30) access, as well as 50 transcatheter aortic valve replacement by CoreValve system were included into the study. Complications including perioperative mortality, total 30-day mortality, as well as post-hospital mortality were registered during aortic valve replacement, immediately after surgery, before the expiry of 30 days. Mean follow-up was 2.2 years (range 0.2 to 5.2 years).Results. Hospital mortality was on average 6.9%. 121 patients had been discharged from the department after the surgery. The number of deaths in the post-hospital period was 14.8%. Valve type and the type of access had no effect on post-hospital mortality. Men died more than 2.5 times often than women, regardless of age. Atrioventricular block, pacemaker implantation, and history of chronic obstructive pulmonary disease were the most significant prognostic factors. An important role of minor stroke and renal failure should be noted. Mortality did not depend on the surgical access or valve type. All parameters characterizing the intervention were significantly associated with mortality, both during and after surgery. The proportion of survivors at the end of the first year of observation using Corvalve system was 86.9%, Edwards valve by transfemoral access - 88% and Edwards valve by transapical access – 85.4% (insignificant differences for all groups, p>0.05). Two-year survival was 77.5%, 82.5% and 82.7%, respectively (also insignificant differences for all groups, p>0.05).Conclusion. TAVI is the method of choice, reasonable alternative approach for surgical valve replacement in patients with high surgical risk, although mortality after TAVI is still quite high and amounted to 6.9% in our study. It makes it possible to extend life and improve its quality that is of great social importance in the global trend of an aging population.